In silico structural analysis of the complex BRI1 Receptor like Kinase, Pamp Brassinolide and Serk1 Co-Receptor - Naurin, Mehnaz Nafisa (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2021.